The Association Between Knowledge About Gout Arthritis with NSAID and Allopurinol Consumption in Rumah Susun Penjaringan - Brigita Naomi Santoso; Erfen Gustiawan Suwangto; Maria Riastuti Iryaningrum (Faculty of Medicine, Public Health, and Nursing, 2021)
Background: Health ministry is one of ministries in Indonesia who needs high fund every year. It is used for national health, starting from the availability of health infrastructure to the availability of medicine in health primary care and hospital. In Indonesia, there is a myth that joint pain is gout arthritis. In Indonesia, 71% people who have joint pain buy pain killer without going to get an examination by doctor first. Therefore, a research about the relationship between knowledge about gout arthritis and NSAID and Allopurinol consumption in Rumah Susun Penjaringan. Objective : Knowing if there is association between knowledge about gout arthritis and NSAID and Allopurinol consumption. Methods : This research used cross sectional study and involved 68 people in Rumah Susun Penjaringan. Result : There is no significant relationship between knowledge about gour arthritis with NSAID (p = 0.234) and Allopurinol (0.666) consumption in Rumah Susun Penjaringan. Conclusion : There is no relationship between knowledge about gout arthritis with NSAID and Allopurinol consumption in Rumah Susun Penjaringan.